Development of a Question Prompt List as a Communication Intervention to Reduce Racial Disparities in Cancer Treatment - Eggly, Susan (2013)
Racial disparities have been found in the use of chemotherapy as cancer treatment. These disparities may be, in part, due to well-documented differences in the quality of communication during clinical interactions with oncologists and Black versus White patients. In this study using a Community-Based Participatory Research (CBPR) approach, academic researchers, community members, and oncologists formed a partnership to develop a communication intervention to address racial disparities in cancer care. Partners developed a Question Prompt List (QPL), a simple tool that can be used to improve communication, and thus treatment, during clinical interactions in which oncologists and Black patients discuss chemotherapy. Partners endorsed the use of a QPL, provided specific suggestions for content and format, conducted and analyzed qualitative interviews with Black patients receiving chemotherapy, and approved the final version. The feasibility and effectiveness of the QPL that resulted from this research process are currently under evaluation in a separate study.